Imagining Bodies in the Work of Dionne Brand (Altre Modernità, 2009)
This essay explores the interface between the re-writing of history and the re-writing of the history of sexuality in the poetry and fiction by the Caribbean-Canadian writer Dionne Brand. Starting from her poetry book No Language Is Neutral (1990), as the first work in which she openly deals with lesbian love and sexuality, and closing with her novel At the Full and Change of the Moon (1999), this paper traces the narrative of non-heterosexual love and desire in Dionne Brand’s work, reading the representation of the racialized and sexed body in Brand’s writing in the light of Merleau-Ponty’s philosophy of the body.